2010
DOI: 10.1159/000253871
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Pancreatic Neuroendocrine Tumors: Report of 112 Cases

Abstract: Objectives: To review the clinical data of a group of patients with pancreatic neuroendocrine tumors (pNETs) and to investigate the role of surgery in the treatment for pNETs by analyzing clinical manifestations and postoperative course of this rare disease. Methods: A total of 112 patients (aged 21–76 years; 45 males) who underwent treatment between 1980 and 2003 were recruited in this study. Patients’ data related to demographics and characteristics, diagnostic studies, surgical and tumor characteristics and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…TMN stage was mentioned in 4 articles 18 , 22 , 24 , 25 . On the basis of current knowledge, people with advanced TMN stage are more likely to have a negative outcome.…”
Section: Resultsmentioning
confidence: 99%
“…TMN stage was mentioned in 4 articles 18 , 22 , 24 , 25 . On the basis of current knowledge, people with advanced TMN stage are more likely to have a negative outcome.…”
Section: Resultsmentioning
confidence: 99%
“…Gao et al [18] found that the overall 5-year actual survival rate of patients with well-differentiated neuroendocrine carcinoma was 56%, significantly less than patients with well-differentiated neuroendocrine tumor (91%; p=0.001). All the patients of poorly differentiated neuroendocrine carcinoma died in 5 years.…”
Section: Discussionmentioning
confidence: 98%
“…Microangioinvasion has been described as risk factor for metastases in rectal NETs [32]. In patients with pancreatic NET microangioinvasion was associated with higher risk of recurrence [33] and shorter long-term survival [34]. In the study of Boninsegna et al [15], microangioinvasion was predictive for recurrence in univariate analysis but failed to be confirmed as independent predictive parameter in multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%